Resistance of Material: Theoretical Mastery over the Literary Text - Bekavac, Luka (Poznańskie Studia Slawistyczne, 2013)
After a brief account of Derrida’s notion of singularity as an irreducible, quasi-material layer of (literary) texts, this article attempts to delineate its effects on theoretical or scientific mastery over literature. Invention and law are examined as necessary but mutually cancelling origins of aesthetic and scientific institutions, and the final chapter – following Derrida’s Ulysse gramophone – questions the limits of theoretical competence in collision with the incalculable swerve of literarity.